THE INFLUENCE OF CUSTOMER SATISFACTION AND BRAND TRUST ON BRAND SWITCHING OF GLOBAL FASHION BRANDS TOWARDS LOCAL FASHION BRANDS - Alifah Fridayanti, Sarah
Currently, the local fashion brand in Indonesia is rising. The number of local fashion brands is increasing because their existence is able to compete with global fashion brands, allowing customers to easily switch from global to local fashion brands. The preliminary survey supported the issues with the majority of the respondents considering themselves doing brand switching from global to local fashion brands and in the past years they tended to buy fashion items from local fashion brands. The purpose of this study is to know the factors influencing Indonesian customer brand switching behavior. Moreover, a previous study found that customer satisfaction is known as the primary reason of customer’s doing brand switching. Therefore, this study also researched the influence of customer satisfaction on brand trust, and to know the influence customer’s variety seeking behavior on brand switching intentions of global fashion brands towards local fashion brands. A quantitative approach is performed in this study through an online survey which received 266 respondents with a specific criteria. Descriptive analysis and PLS-SEM is used to analyze the gathered data. The findings show that the factors influencing customers' brand switching intentions are local identity, brand credibility, brand attitude, customer satisfaction, and brand trust. Customer satisfaction also has a positive influence on customer's brand trust. It is also found that moderating effect of variety seeking also influences the brand switching of global fashion brands towards local fashion brands. This study contributes to filling a gap in the studies of the fashion industry focusing on customer’s brand switching intention of Global Fashion Brands towards Local Fashion Brands. In addition, this study may help the fashion industry, especially global fashion brands operating in Indonesia that compete with Indonesian local fashion brands to gain in-depth knowledge of Brand Switching as well as assist them by providing marketing strategies.